The Influence of Green Knowledge Sharing, Green Innovation, and Green Creativity on the Competitive Advantage of Green MSMEs - Bias Bianglala; Audita Nuvriasari (Arthatama: Journal of Business Management and Accounting, 2026)
The increasing environmental concerns and the demand for sustainable business practices have encouraged green MSMEs to develop strategies that support long-term competitiveness. This study aims to analyze the influence of green knowledge sharing, green innovation, and green creativity on the competitive advantage of Green MSMEs in the Special Region of Yogyakarta. The sample in this study is 100 respondents who are owners or managers of green MSMEs in the Special Region of Yogyakarta, which were determined using purposive sampling techniques. The analysis method used in this study is multiple linear regression analysis. The results show that green knowledge sharing, green innovation, and green creativity have positive and significant effects on the competitive advantage of green MSMEs in the Special Region of Yogyakarta. This study concludes that green knowledge sharing, innovation, and creativity play important roles in strengthening the competitive advantage of green MSMEs. The contribution of this study provides practical insights for green MSMEs to improve sustainable business strategies and supports the development of green entrepreneurship.